2009
DOI: 10.1039/b912607d
|View full text |Cite
|
Sign up to set email alerts
|

Second-order perturbation theory with complete and restricted active space reference functions applied to oligomeric unsaturated hydrocarbons

Abstract: Multiconfigurational second-order perturbation theory based on either a complete active space reference wave function (CASSCF/CASPT2) or a restricted active space reference wave function (RASSCF/RASPT2) has been applied to compute one-electron ionization potentials and vertical electronic energy differences of oligomers of length n formed from ethylene (n = 1-10), acetylene (n = 1-5), and phenylene (n = 1-3) subunits. The RASSCF/RASPT2 approach offers an accuracy similar to CASSCF/CASPT2 at significantly reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 72 publications
2
44
0
Order By: Relevance
“…Available CASPT2 calculations give excitation energies in the range 6.1−6.3 eV, 3,14,18 but these single-state studies are hard to compare as they employ different zero-order Hamiltonians 14,18 or, in the presence of diffuse functions, lead to a too diffuse state due to the lack of a multistate treatment of the close Rydberg state. 3 Various flavors of CC calculations yield values between 6.2 and 6.4 eV.…”
Section: Introductionmentioning
confidence: 99%
“…Available CASPT2 calculations give excitation energies in the range 6.1−6.3 eV, 3,14,18 but these single-state studies are hard to compare as they employ different zero-order Hamiltonians 14,18 or, in the presence of diffuse functions, lead to a too diffuse state due to the lack of a multistate treatment of the close Rydberg state. 3 Various flavors of CC calculations yield values between 6.2 and 6.4 eV.…”
Section: Introductionmentioning
confidence: 99%
“…15 They ascribed the ordering anomaly to the electron correlation effects. Since then, there have been continuous and considerable investigations, such as by Tavan and Schulten, 16 Cave and Davidson, 17 Nakayama et al, 18 Hsu et al, 19 Serrano-Andres et al, 20 Starcke et al, 21 Marion and Gilka, 22 Shahi et al, 23 in calculating the 2A g /1B u orderings for the short unsubstituted polyene and Shukla 24 for the substituted polyene [poly(diphenylacetylene)]. It is found that the 2A g state has important contributions from electron double excitation configuration in the molecular orbital picture.…”
Section: Introductionmentioning
confidence: 99%
“…[40][41][42][43][44][45] To address this issue, a second-order perturbation method (ORMAS+PT2) is under development.…”
Section: Discussionmentioning
confidence: 99%